(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
This article dwells in detail on the term phraseology and provides information about their degree of intensification. Also, the article examines the specific features of phraseological units in the English language, their comparative analysis in both languages is carried out, and the functional-pragmatic aspect of phraseology is studied.